Physical activity for adults: Physical Activity Guidelines for the Brazilian Population - Ritti-Dias, Raphael (2021)
In 2020, the Brazilian Health Ministry in partnership with the Federal University of Pelotas, Rio Grande do Sul selected researchers for the elaboration of the Brazilian Physical Activity Guide. The objective of this article was to present the methods used as well as the results of the Brazilian Physical Activity Guide for adults from 18 to 59 years of age. The construction of the guide was based on four guiding questions: What, when, why and how to practice physical activity? To answer these questions, two main strategies were adopted: review of scientific evidence and “listening” to different strategic groups. From the procedures performed, it is recommended that adults accumulate between 150 and 300 minutes of physical activity per week of moderate intensity and / or between 75 and 150 minutes per week of vigorous intensity, regardless of the type (aerobics or muscle strengthening). Among the identified benefits, the reduction of mortality due to chronic diseases, improvement in mental health, in social and emotional aspects stands out, (e.g., interaction with other people, contact with local culture etc.) and emotional (e.g., self-esteem, feeling of well-being etc.). In addition, the recommendations were not restricted to the aforementioned outcomes, we sought to consider the specificities and singularities of the adult population in different regions of Brazil. The guide also presents messages to overcome the main barriers of physical activity, and the existing support networks to help Brazilian adults to have a more physically active life.